EVALUATION OF AN INTRINSIC AND A SPECIFIC VULNERABILITY ASSESSMENT METHOD IN COMPARISON WITH GROUNDWATER SALINISATION AND NITRATE CONTAMINATION LEVELS IN TWO AGRICULTURAL REGIONS IN THE SOUTH OF PORTUGAL - Stigter T.Y.; Ribeiro L.; Dill A.M.M.C. (My University, 2006)
The applicability of two vulnerability assessment methods in evaluating the impact of agricultural activities on groundwater quality, is tested in two areas in the south of Portugal with modest results. Intensive citri- and horticulture require large amounts of fertiliser and water supplied by irrigation, which induces groundwater salinisation and contamination by nitrates. The degree of contamination varies highly within and between the study areas and is related to hydrogeological factors as well as intensity of agricultural practices. Vulnerability mapping is performed with the intrinsic DRASTIC method and the specific Susceptibility Index (SI), which is an adaptation of DRASTIC. These methods can constitute useful groundwater management tools, for instance when designating new Nitrate Vulnerable Zones as defined in the European Directive 91/676/EEC. However, in the case of DRASTIC, little correspondence exists between the most vulnerable and the most contaminated areas. This is mainly a result of underestimating the dilution capacity and overemphasising the attenuating potential of the unsaturated zone and aquifer, as both chloride and nitrate prove to be very stable contaminants. By including a parameter for land use, SI manages to produce more reliable results, although in many areas the vulnerability is overestimated.
Keywords: VULNERABILITY; CONTAMINATION; AGRICULTURE; DILUTION; PORTUGAL